Epistemologi Komparatif Linguistik Timur dan Barat: Studi Genealogi Pemikiran Tamam Hasan dan Noam Chomsky - Salsabila Nafisa'ah; Ismaliah; Cholivea Ilmi Balesta; Mauidlotun Nisa’; Wati Susiawati (Kopertais Wilayah I DKI Jakarta dan Banten, 2026)
This study examines the epistemological tension between Eastern and Western linguistic traditions by comparing the ideas of Tammam Hassan and Noam Chomsky as two major figures in contemporary linguistics. The aim of this research is to identify the epistemological differences and points of convergence between the two scholars, as well as to assess the contribution of each tradition to the development of modern linguistic thought. This study employs a library research method and a descriptive comparative analytical approach by reviewing primary works and secondary studies related to both figures. The findings indicate that the Eastern tradition, rooted in the Arab Islamic intellectual heritage, conceives language as a semantic and contextual phenomenon inseparable from texts, speech situations, and networks of linguistic and non-linguistic cues. This approach finds its modern formulation in Hassan’s theory of tadafur al-qara’in. In contrast, the Western tradition from Saussurean structuralism to Chomskyan generative linguistics positions language as a formal system and a mental capacity explained through abstract models and internal rules. The comparison reveals fundamental differences in how linguistic data, structure, and sources of linguistic knowledge are understood. However, the study also emphasizes that the two approaches are complementary. The integration of structural mental dimensions with semantic contextual perspectives opens new possibilities for developing linguistic theories that are more comprehensive, multidisciplinary, and aligned with the complexity of human language.